Ti: Genetic diversity assessment of Koompassia malaccensis - Lee, Chai Ting; Lee, Soon Leong; Qamaruz Zaman, Faridah; Siraj, Siti Shapor; Ng, Kevin Kit Siong; Muhammad, Norwati (Universiti Putra Malaysia Press, 2008)
A genetic diversity study of Koompassia malaccensis based on 19 populations from 18 forest reserves in Peninsular Malaysia is reported. The genetic diversity assessment was based on six polymorphic microsatellites. Overall, all the populations showed high levels of genetic diversity. The allelic richness ranged from 6.0 (Pekan) to 9.3 (Lenggor) whereas the gene diversity ranged from 0.683 (Pekan) to 0.859 (Lenggor). The estimated coefficient of population differentiation (R st) was 0.07, implying that 93% of the genetic diversity was partitioned within populations, with only 75% distributed among populations. From the cluster analysis among the populations, the two peat swamp populations (Pekan and Kuala Langat Selatan) formed a tight cluster even though they are not adjacuet to one another. Further analysis including more populations and applying more microsatellites will generate more comprehensive genetic information.